Socio-economic inequalities in the association between diabetes and labour force participation in Germany: A repeated cross-sectional study - Mackowiak, Malwina M.; Brinks, Ralph; Hoyer, Annika; Linnenkamp, Ute; Piedboeuf-Potyka, Katharina; Neuhäuser, Markus; Kuss, Oliver; Tönnies, Thaddäus (GMS German Medical Science, 2025)
Objective: Diabetes is associated with lower labour force participation. The proportion of people having diabetes is higher among people with a low socio-economic position. We aimed to describe socio-economic differences in the association between diabetes and labour force participation in Germany. Methods: Based on repeated cross-sectional data from the German Socio-Economic Panel Study, the probability for participating in labour force was modelled with a logistic regression model including diabetes status, sex, socio-economic position, survey year and age as independent variables. Analyses accounted for the complex survey design of the study and used post-stratification weights. For easier interpretation, we estimated relative risks instead of odds ratios from logistic regression using post-estimation techniques. Relative labour force participation shortfall [%] was calculated as (1 – relative risk) x 100. Results: Labour force participation among people without diabetes was 82.2% compared to 55.9% among people with diabetes. Labour force participation shortfall was higher for low socio-economic position values and decreased with increasing socio-economic position. Labour force participation shortfall was generally larger among women while the association between labour force participation shortfall and socio-economic position was stronger among men. Conclusions: Diabetes-associated labour force participation shortfall mainly affects people with low socio-economic position, which indicates that this population subgroup not only carries a higher risk of diabetes, but also might be more strongly affected by its negative impact on productivity. Future studies aiming to quantify diabetes-associated productivity losses should take associations specific to socio-economic position into account.